Hubungan Sistem Informasi Manajemen Kepegawaian (SIMPEG) Dengan Kualitas Pelayanan Administrasi Kepegawaian - Karina Karina; Tatang Ibrahim; Dian Dian (J-MPI (Jurnal Manajemen Pendidikan Islam), 2022)
Personnel management information system (SIMPEG) is a system used to store employee data, one of the institutions that has implemented a personnel management information system (SIMPEG) as a system for storing employee data and facilitating services is the Office of the Ministry of Religion of West Bandung Regency. This study aims to find out: 1) how is the personnel management information system (SIMPEG) at the office of the Ministry of Religion of West Bandung Regency, 2) how is the quality of personnel administration services at the office of the Ministry of Religion of West Bandung Regency, 3) how is the relationship between the personnel management information system (SIMPEG) with the quality of personnel administration services at the office of the Ministry of Religion of West Bandung Regency. This research is descriptive, using a quantitative approach, the type of correlation. The data collection technique used is a questionnaire questionnaire. Then the data analysis techniques in this research are instrument test (validity and reliability), partial indicator analysis test, prerequisite test (normality and linearity test), and correlation test. Based on the results of the questionnaire distribution, the variable category x (SIMPEG) includes high qualifications with an average score of 4,54. Based on the results of the questionnaire distribution, the variable y (quality of personnel administration services) includes high qualifications with an average value of 4,41. The relationship between the personnel management information system (SIMPEG) and the quality of personnel administration services based on correlation testing, the results obtained from the correlation coefficient of 0,674 This shows that the relationship between the personnel management information system variable and the quality of personnel administration services, the strength level is at 0,674, so it can be interpreted these results are in the category 0.60 – 0.79, it can be interpreted that between these variables have a strong relationship.